2015
DOI: 10.1016/j.drugalcdep.2015.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of minimum legal drinking age laws on marijuana and other illicit drug use in adulthood

Abstract: Background Exposure to permissive minimum legal drinking age (MLDA) laws (ability to purchase alcohol <21 years) during adolescence can have long-term effects, including heavy alcohol use or alcohol use disorders as adults. We examined whether exposure to permissive MLDA laws during adolescence has long-term effects on illicit drug use and disorders in adulthood. Methods Participants from the 2004-2012 National Survey of Drug Use and Health (NSDUH) were linked with historical state MLDA laws. Participants bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Furthermore, the rate of misclassification is much lower than the rate of emigration as individuals may move to states with the same MLDA and thus migrate without changing their policy exposure. Elsewhere, using population migration data, we have estimated that misclassification to be approximately 11% (Krauss et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the rate of misclassification is much lower than the rate of emigration as individuals may move to states with the same MLDA and thus migrate without changing their policy exposure. Elsewhere, using population migration data, we have estimated that misclassification to be approximately 11% (Krauss et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…First, MLDA exposure is determined by a person's year of birth and state of residence between the ages of 18 to 21, but it is not possible to directly observe this from mortality data. Instead, we must rely on subject's state of residence at time of observation as a proxy (Krauss et al., ; Norberg et al., ; Plunk et al., , ). To determine whether this is a reasonable way to estimate policy exposure, we conduct a separate set of analyses on “likely nonmovers.” This subset of the study sample resided in their birth state at time of observation and are much less likely to have ever migrated between states.…”
mentioning
confidence: 99%
“…The ambivalence of the evidence—including studies that indicate asymmetrical, limited, or non-existent associations between alcohol use and other drug consumption (Krauss, Cavazos-Rehg, Agrawal, Bierut, & Grucza, 2015; Petry, 2001; White et al, 2015)—calls for further research using different methodologies to understand these relations. Examining these hypotheses at the individual level represents such an advance in our understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-five studies were found which reported information (37 units of information) on the impacts of an increase in an MLDA on primary societal impacts (i.e., drinking, possession and purchasing patterns of alcohol) [ 44 , 45 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Thirty-seven units of information were found, since 2 of the 35 studies reported information on multiple types of primary societal impacts, finding significant/relevant impacts in some cases and finding no impact in others.…”
Section: Resultsmentioning
confidence: 99%